Collaboration between Parents and the Community in Implementing an Islamic Values-Based Curriculum at RA Nurul Huda - Devi Sulaeman (MASI Mandiri Edukasi, 2026)
The implementation of an Islamic values-based curriculum requires collaboration between schools, parents, and the wider community. The research problem in this study concerns the extent of parental and community participation in supporting the implementation of a flexible and responsive curriculum that meets students’ needs at RA Nurul Huda. This study aims to describe and analyze the forms and levels of collaboration between parents and the community in supporting the implementation of an Islamic values-based curriculum. The research employed a descriptive qualitative method, with data collected through in-depth interviews with 15 parents and 10 community members who had relevant experience and knowledge. The findings indicate that parents and community members generally provide positive support for the implementation of the Islamic values-based curriculum, both through moral support and participation in school activities. However, several challenges remain, including limited awareness of the importance of Islamic education and limited capacity to support a flexible curriculum effectively. Therefore, this study recommends strengthening commitment, increasing awareness, and empowering parents and the community to optimize the implementation of the Islamic values-based curriculum at RA Nurul Huda.